Assessing the contribution of farmers' cooperative towards effective sugar supply chain in Ratchaburi, Thailand - Piya Wongwalaimas; Shivakoti, Ganesh P.; Athapol Noomhorm; Soni, Peeyush; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
Cooperative is one of the most crucial factors to contribute the effective of supply chain by reducing wasted transaction, creating added value, and redistributing benefits to members of cooperative. Especially, sugarcane, which is one of significant export goods, is a cash crop which has a lot of problems in industry{u2019}s supply chain such as revenue-sharing systems, planted credits provided by sugar mills, insufficient harvested labors, and etc. From several literatures, all these problems which are inevitable problems in sugarcane{u2019}s supply chain are certainly required bargaining powers and knowledge sharing in implementing with cooperative. There are 3 main objectives in this research; 1. To assess the successes of cooperative in sugar cane cooperative members and non-cooperative members. 2. To assess bargaining power and knowledge sharing in sugar cane cooperative members and non-cooperative members. 3. To examine the relationship of bargaining power and knowledge sharing affect the successes of cooperative. This research is a casual research study for causes and effects of bargaining powers and knowledge in implication of successes of cooperative. This research was conducted as a cross-sectional analysis by using group of contract sugarcane growers (non-cooperative members) and members of cooperative. In results and discussions, this research was expressed in descriptive statistics for reviewing nominal data and was utilized independent variable T-test, ANOVA, and correlation matrix in comparing significantly statistical difference between cooperative group and non-cooperative group.The results was presented cooperative was tend to be more success than quota systems in 7 of 8 indicators of successes of cooperative. Bargaining powers of cooperative{u2019}s members were evidently higher than non-members of cooperative. However, knowledge sharing was the weak point of cooperative system. Moreover, the successes of cooperative would be followed to the indicators that would be added the marginal profits to farmers.
A thesissubmitted in partial fulfillment of the requirements for the degree of Master of Agribusiness Management, School of Environment, Resources and Development
Thesis (M. Am.) - Asian Institute of Technology, 2014
Keywords: Sugarcane -- Thailand -- Ratchaburi; Sugarcane industry -- Thailand